2023
DOI: 10.1088/1361-6560/acc926
|View full text |Cite
|
Sign up to set email alerts
|

Intra-brain vascular models within the ICRP mesh-type adult reference phantoms for applications to internal dosimetry

Abstract: Objective: Phantoms of the International Commission on Radiological Protection provide a framework for standardized dosimetry. The modeling of internal blood vessels – essential to tracking circulating blood cells exposed during external beam radiotherapy and to account for radiopharmaceutical decays while still in blood circulation – is, however, limited to the major inter-organ arteries and veins. Intra-organ blood is accounted for only through the assignment of a homogeneous mixture of parenchyma and bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It was concluded that proton treatments are not necessarily advantageous in terms of dose to the blood even though they are associated with a lower integral dose because of the importance of the beam-on time. Similar vascular tree models have been developed for the brain ( 89 ) and lung ( 90 ). Such organ-specific vasculature models can be combined with a Markov chain approach to link them to whole body blood flow based on reference values for cardiac output and organ blood volumes ( 23 , 24 ).…”
Section: Estimating the Dose To The Blood And To Circulating Lymphocy...mentioning
confidence: 99%
“…It was concluded that proton treatments are not necessarily advantageous in terms of dose to the blood even though they are associated with a lower integral dose because of the importance of the beam-on time. Similar vascular tree models have been developed for the brain ( 89 ) and lung ( 90 ). Such organ-specific vasculature models can be combined with a Markov chain approach to link them to whole body blood flow based on reference values for cardiac output and organ blood volumes ( 23 , 24 ).…”
Section: Estimating the Dose To The Blood And To Circulating Lymphocy...mentioning
confidence: 99%